Hakikat Manusia sebagai Pelaku Pendidikan Islam - Bima Fandi Asy'arie; Abd. Haris (Prodi Pendidikan Agama Islam IAI Al-Qodiri Jember, 2023)
Educators are people who teach or carry out educational activities. Educators as controllers, directors, and guides the process that directs human development and growth. In building the relationship between teacher and student is the educator's most important task. Meanwhile, students are individuals who will receive education from a teacher. Being a good teacher requires qualities that include courage, self-confidence, dependability, and respect for others. Teachers must also have pedagogical, professional, personality, and social abilities. The research is qualitative in nature using the method of library research (library research). In the literature study method, this is done by preparing a research framework. The purpose of this research is to find out the nature of educators in Islamic education, and the nature of students in Islamic education). The results in this study include (1) the definition of educators, the duties of educators, the characteristics of education, the competence of educators, and the responsibilities of educators. (2) the definition of students, the duties and responsibilities of students, and the ethics of students.